2016
DOI: 10.5152/npa.2015.10003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Greater Occipital Nerve Blocks in Migraine Prophylaxis

Abstract: This study showed significant decreases in headache parameters in both groups. As GON blocks were performed in patients unresponsive to medical prophylaxis, a decrease in the headache parameters in Group PGON similar to that in Group GON can be attributed to GON blocks. Consequently, these results show that repeated GON blocks with local anesthetic can be an effective alternative treatment in migraine patients who are unresponsive to medical prophylaxis or who do not prefer to use medical prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Even though we are lacking randomized double-blinded comparative study for ON using ONB method, there is well-documented evidence on the efficacy of the ONB as potential management tool for cervicogenic and cluster headaches ( 23 , 24 ). Similarly, new reports about clinical application of local anaesthetic injections for migraine-type headaches are emerging and implying satisfactory outcomes ( 25 , 26 ). This positive effect of ONB applicability in a wide range of headache disorders is exceeding the half-life of local anaesthetics and is attributed to the changes in nociceptive pathways in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Even though we are lacking randomized double-blinded comparative study for ON using ONB method, there is well-documented evidence on the efficacy of the ONB as potential management tool for cervicogenic and cluster headaches ( 23 , 24 ). Similarly, new reports about clinical application of local anaesthetic injections for migraine-type headaches are emerging and implying satisfactory outcomes ( 25 , 26 ). This positive effect of ONB applicability in a wide range of headache disorders is exceeding the half-life of local anaesthetics and is attributed to the changes in nociceptive pathways in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, opinions differ among practitioners regarding the injection point and non‐target specificity, and this is the greatest disadvantage of the classical approach. Various injection points have been reported such as slightly medial to the SNL rather than palpated along it (Ward, ), 2 cm lateral and 2 cm inferior to the EOP (Inan et al ), the area of greatest tenderness to palpation along the SNL (Tobin and Flitman, ), and 1 ∼ 2 cm below the midpoint of the EOP‐MP line (Afridi et al ). The clinical trend for GON block has been the medial third of the EOP‐MP line (Blumenfeld et al ; Kocer, ; Unal‐Artik et al ), but this was derived from non‐objective evidence of clinical experiences such as success rate and duration of approach rather than objective evidence.…”
Section: Discussionmentioning
confidence: 99%
“…A local anesthetic block of the GON, which is very effective, safe and relatively easy to perform, is the most widely used procedure for diagnosing and alleviating the pain of ON (Inan et al ; Kocer, ). Conventionally, the anesthetic is injected just medial to the OA‐palpated region or the area of greatest tenderness to palpation along the SNL (Tobin and Flitman, ; Greher et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The attack frequency decreased from 15.73 (at baseline) to 4.52 (at month 3) in the GON blockade group versus from 13.76 to 3.28 in the GON blockade + prophylactic medication group, whereas headache severity was reduced from 8.26 to 5.16 in the GON blockade group versus from 8.80 to 5.96 in the GON blockade + prophylactic medication group. There were no serious AEs reported [67] (Table 2(b)). An open-label clinical trial of bilateral GON blockade with bupivacaine (2 mL, 0.5%) for the acute treatment of migraine patients with prolonged or persistent aura (n = 18 patients and 22 episodes with aura) revealed that complete response without early recurrence was achieved in 50% (n = 11) and with 24-h recurrence in 9.1% (n = 2) of the cases, whereas partial (greater than 50%) improvement was achieved in 27.3% (n = 6) of the cases.…”
Section: Open-label Studies Of Gon Blockade With Chemical Agents In Emmentioning
confidence: 96%